Low‐intensity pulsed ultrasound alleviates doxorubicin‐induced cardiotoxicity via inhibition of S100a8/a9‐mediated cardiac recruitment of neutrophils - Hong Zhu; Min He; Yong‐Li Wang; Yuanxin Zhang; Jingsong Dong; Bo‐Yan Chen; Yu‐Lin Li; Lu‐Jun Zhou; Lin‐Juan Du; Yuan Liu; Wu‐Chang Zhang; Dean Ta; et al. (Wiley, 2023)
Abstract Doxorubicin (DOX)‐induced cardiotoxicity limits its broad use as a chemotherapy agent. The development of effective and non‐invasive strategies to prevent DOX‐associated adverse cardiac events is urgently needed. We aimed to examine whether and how low‐intensity pulsed ultrasound (LIPUS) plays a protective role in DOX‐induced cardiotoxicity. Male C57BL/6J mice were used to establish models of both acute and chronic DOX‐induced cardiomyopathy. Non‐invasive LIPUS therapy was conducted for four consecutive days after DOX administration. Cardiac contractile function was evaluated by echocardiography. Myocardial apoptosis, oxidative stress, and fibrosis were analyzed using terminal deoxynucleotidyl transferase‐mediated dUTP nick end labelling (TUNEL) staining, dihydroethidium (DHE) staining, and picrosirius red staining assays. RNA‐seq analysis was performed to unbiasedly explore the possible downstream regulatory mechanisms. Neutrophil recruitment and infiltration in the heart were analyzed by flow cytometry. The S100a8/a9 inhibitor ABR‐238901 was utilized to identify the effect of S100a8/a9 signaling. We found that LIPUS therapy elicited a great benefit on DOX‐induced heart contractile dysfunction in both acute and chronic DOX models. Chronic DOX administration increased serum creatine kinase and lactate dehydrogenase levels, as well as myocardial apoptosis, all of which were significantly mitigated by LIPUS. In addition, LIPUS treatment prevented chronic DOX‐induced cardiac oxidative stress and fibrosis. RNA‐seq analysis revealed that LIPUS treatment partially reversed alterations of gene expression induced by DOX. Gene ontology (GO) analysis of the downregulated genes between DOX‐LIPUS and DOX‐Sham groups indicated that inhibition of neutrophil chemotaxis might be involved in the protective effects of LIPUS therapy. Flow cytometry analysis illustrated the inhibitory effects of LIPUS on DOX‐induced neutrophil recruitment and infiltration in the heart. Moreover, S100 calcium binding protein A8/A9 (S100a8/a9) was identified as a potential key target of LIPUS therapy. S100a8/a9 inhibition by ABR‐238901 showed a similar heart protective effect against DOX‐induced cardiomyopathy to LIPUS treatment. LIPUS therapy prevents DOX‐induced cardiotoxicity through inhibition of S100a8/a9‐mediated neutrophil recruitment to the heart, suggesting its potential application in cancer patients undergoing chemotherapy with DOX.